Development and piloting of a software tool to facilitate proactive hazard and risk analysis of Health Information Technology. (March 2020) - Habli, Ibrahim; Jia, Yan; White, Sean; Gabriel, George; Lawton, Tom; Sujan, Mark; Tomsett, Clive
Health Information Technology is now widely promoted as a means for improving patient safety. The technology could also, under certain conditions, pose hazards to patient safety. However, current definitions of hazards are generic and hard to interpret, particularly for large Health Information Technology in complex socio-technical settings, that is, involving interacting clinical, organisational and technological factors. In this article, we develop a new conceptualisation for the notion of hazards and implement this conceptualisation in a tool-supported methodology called the Safety Modelling, Assurance and Reporting Toolset (SMART). The toolset aims to support clinicians and engineers in performing hazard identification and risk analysis and producing a safety case for Health Information Technology. Through a pilot study, we used and examined the toolset for developing a safety case for electronic prescribing in three acute hospitals. Our results demonstrate the ability of the approach to ensure that the safety evidence is generated based on explicit traceability between the clinical models and Health Information Technology functionality. They also highlight challenges concerning identifying hazards in a consistent way, with clear impact on patient safety in order to facilitate clinically meaningful risk analysis.